Synthesis and characterization of two new schiff base ligands and their complexes with cobalt(II), nickel(II) and copper(II) - Yazici, A; Akgün, F (Springer, 2006)
Two Schiff base ligands, 2-{E-[(5-phenyl-6H-1,3,4-thiadiazin-2yl)imino]methyne}-1-naphthol ((LH)-H-1) and 5-nitro-2-{[(5-phenyl-6H-1,3,4-thiadiazin-2-yl)imino]methyne}phenol ((LH)-H-2) have been prepared from 5-phenyl-6H-1,3,4-thiadiazin-2-amine (A), 2-hydroxynaphthaldehyde (1) and 2-hydroxy-5-nitrobenzaldehyde (2) Mononuclear Co(II), Ni-II and Cu-II complexes of the ligands have been prepared by using Co-II, Ni-II and Cu-II salts with a 1:2 metal:ligand ratio. It was determined that the bidentate behavior of the ligands is accomplished via the phenolic oxygen and the azomethine nitrogen atoms. The structures of the ligands and their complexes were identified by using elemental analyses, i.r., H-1-n.m.r. spectra, electronic spectra, magnetic susceptibility measurements and thermogravimetric analyses (t.g.a.).
Keywords: Metal-Complexes; Cu(Ii); Co(Ii); Ni(Ii); Zinc(Ii)